2006
DOI: 10.1152/ajprenal.00299.2005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of mice lacking the serum- and glucocorticoid-inducible kinase SGK1 against salt-sensitive hypertension induced by a high-fat diet

Abstract: of mice lacking the serum-and glucocorticoid-inducible kinase SGK1 against salt-sensitive hypertension induced by a high-fat diet. Am J Physiol Renal Physiol 291: F1264 -F1273, 2006; doi:10.1152/ajprenal.00299.2005.-Mineralocorticoids enhance expression and insulin stimulates activity of the serum-and glucocorticoid-inducible kinase SGK1, which activates the renal epithelial Na ϩ channel (ENaC). Under a salt-deficient diet, SGK1 knockout mice (sgk1 Ϫ/Ϫ ) excrete significantly more NaCl than their wild-type lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 81 publications
(101 reference statements)
8
49
0
Order By: Relevance
“…Importantly, fluid intake, urinary flow rate, and urinary sodium chloride excretion was significantly increased in sgk1(Ϫ/Ϫ) mice, and blood pressure was elevated in wild-type but not sgk1(Ϫ/Ϫ) mice (70). These experiments demonstrate an important role of Sgk1 in the hypertensive effects of a combined high-fat/high-salt diet, probably by the combined action in glomeruli, distal tubules, and proximal tubular cells.…”
Section: Potential Role Of Impaired Corticosteroid Regulation In Westmentioning
confidence: 68%
See 1 more Smart Citation
“…Importantly, fluid intake, urinary flow rate, and urinary sodium chloride excretion was significantly increased in sgk1(Ϫ/Ϫ) mice, and blood pressure was elevated in wild-type but not sgk1(Ϫ/Ϫ) mice (70). These experiments demonstrate an important role of Sgk1 in the hypertensive effects of a combined high-fat/high-salt diet, probably by the combined action in glomeruli, distal tubules, and proximal tubular cells.…”
Section: Potential Role Of Impaired Corticosteroid Regulation In Westmentioning
confidence: 68%
“…It has been shown that a high-fat/high-salt diet stimulated renal Sgk1 expression in mice (70). Importantly, fluid intake, urinary flow rate, and urinary sodium chloride excretion was significantly increased in sgk1(Ϫ/Ϫ) mice, and blood pressure was elevated in wild-type but not sgk1(Ϫ/Ϫ) mice (70).…”
Section: Potential Role Of Impaired Corticosteroid Regulation In Westmentioning
confidence: 99%
“…For instance, insulin has been shown to modulate the blood pressure response to aldosterone (30), and decrease in plasma aldosterone could contribute to the change of blood pressure with weight loss and resulting plasma insulin reduction (31). Also, in studies conducted in hyperinsulinemic rodents, a lack of aldosterone suppression by salt has been demonstrated (32). Relevant to this issue, it should be noticed that, in our study, systolic blood pressure had a weaker relationship with plasma aldosterone than diastolic blood pressure, as a likely result of its greater intrinsic variability.…”
Section: Discussionmentioning
confidence: 99%
“…141 Two models of hyperinsulinemia and hypertension in mice reveal a role for insulin-dependent SGK1 activation and ENaC-mediated sodium reabsorption. 142,143 Increased apical targeting of ENaC subunits is seen in sodium avid states such as certain models of nephrotic syndrome or cirrhosis. 144 …”
Section: Kidneymentioning
confidence: 99%